Over-winter Survival of Northern Bobwhite in Relation to Landscape Composition and Structure - R. Douglass Holt; Loren W. Burger Jr.; Bruce D. Leopold; Dave Godwin (National Quail Symposium Proceedings, 2017)
The conceptualization of security of bobwhite during winter has been predicated on the assumption that winter ranges differ in quality, based on habitat structure, composition, or interspersion. Although some studies have qualitatively related habitat composition to survival, no studies have quantitatively linked habitat or landscape characteristics to winter survival and the specific structural or compositional characteristics that influence quality are unknown. To quantify winter habitat quality, we modeled hazards as a function of habitat characteristics in relation to winter survival of radio-marked bobwhite (2000, n = 118 in 16 coveys; 2001, n = 49 in 7 coveys) in a managed agricultural landscape in Mississippi, as a function of landscape structure and composition at 2 spatial scales (daily and seasonal ranges). For each spatial scale we constructed a priori models that estimated year-specific winter survival as a function of unique combinations of variables that characterized landscape composition and structure and had previously been identified as relevant to bobwhite ecology. At the spatial scale of winter ranges, the a priori model containing % of landscape, mean patch size, and edge density of linear herbaceous was the best approximating model and suggested a negative effect of linear herbaceous cover on survival. In retrospective analyses, models containing variables describing quantity and structure of linear herbaceous cover and cropland indicated that as these elements increased, risk of mortality increased. At the spatial scale of daily activity, metrics describing landscape structure and composition were poor predictors of survival. During this study, the quantity, patch size, amount of edge, or interspersion of patch types within the winter range or surrounding daily activity locations did not measurably influence the hazard function, suggesting that seasonal ranges can have different composition and structure, yet produce similar survival rates for the birds that inhabit each range.
Keywords: Colinus virginianus; landscape composition; landscape structure; northern bobwhite; survival; winter habitat